Human Resources Information System Impact on Organization Performance: The Roles of Human Capital and HR Analytics (Global Journal of Management and Business Research, 2022)
The purpose of this study is to investigate the mediating role of Human Capital and the moderating role of HR Analytics in the relationship between HRIS and organizational performance in Telecommunication private sector firms in Egypt. A structured questionnaire was administered to survey managers and employees in the three main private telecommunication firms in Egypt. 740 questionnaires were distributed, 472 of which were returned and considered valid. Data was statistically analyzed using structural equation model estimation.
Keywords: HRIS; Human Capital (HC); HR Analytics; organization performance (OP)